Land use in acid sulphate soils degrades river water quality – Do the biological quality metrics respond? - Vehanen, Teppo; Sutela, Tapio; Aroviita, Jukka; Karjalainen, Satu-Maaria; Riihimäki, Juha; Larsson, Aron; Vuori, Kari-Matti (Elsevier BV, 2022)
Land use in the Acid Sulphate (AS) soils induces metal and acidity pollution of aquatic ecosystems in coastal areas worldwide. Increasing utilization of AS soils poses increasing risks for deterioration of water bodies. We studied the effects of the coverage of AS soils, together with other catchment land cover attributes, on aquatic assemblages of fish, diatoms and benthic invertebrates in 42 sites along 15 lowland rivers in Finland during three subsequent years. Low pH and increasing content of several metals in the river water were related to high amount of AS soils in the catchment. Especially increasing iron content and water color were correlated to amount of forested areas in the catchment, whereas lower water color values and higher arsenic, chromium and iron concentrations were associated with wetlands. The assemblage structure of all three biological groups was strongly spatially structured among rivers and varied less temporally. The spatial structure of fish and diatoms were strongly affected by the acidic water, whereas invertebrates were more affected by low alkalinity and increasing concentrations of organic matter and iron. Especially fish and benthic invertebrate bioassessment metrics demonstrated for AS soil induced degradation in acidity by responding to low pH and high acidity, while the response from the diatoms index was weaker. The high metal concentrations alone did not seem to add to the degradation in biometrics without further increase in acidification. Our results highlight the importance of recognizing AS soil areas in the catchment to target the mitigation effects. A holistic approach in the mitigation of the adverse effects from AS soils is needed, using several mitigation methods in the catchment, and directing main efforts and protection from human disturbance to catchment areas with the highest proportion of AS soils. Our results suggest that status assessment of AS rivers should be based on multiple biological quality elements and that their metrics could be improved for better detection of impacts from acidity and metal pressures. The effects of metals and their concentrations on aquatic assemblages should be further examined.
Keywords: acidification; acid deposition; land use; water framework directive; fish fauna; invertebrates; diatoms